SURVIVABILITY USAHA MIKRO KECIL DAN MENENGAH, ADOPSI MEDIA SOSIAL SEBAGAI MEDIA PEMASARAN - Permadi, Indra; Fathussyaadah, Eva (2021)
Social media is an effective means of communication in building marketing communications. The use of social media as a marketing platform must be utilized by MSME entrepreneurs in Indonesia, in increasing survivability and maximizing sales. As a strategic sector, MSMEs must be able to compete in the era of economic digitalization. The theoretical model uses the Technology, Organizational, Environment (TOE) framework, to measure the factors of social media use by MSME business actors, and how the effectiveness of social media platforms as marketing media.The conclusive method used in the research approach aims to test the basic assumptions that have been formulated. The data used in this study are primary data as respondents for MSME business actors, and based on the characteristics of the availability of the data used is Cross Section data. The research population of micro and small business owners, the sampling technique used is probability sampling.